World economy - "Mc Cormick, B. J." (New Delhi, 1989)
Taking as his starting point the rising grain and oil prices of the 1970s, the author explores the patterns of trade and development before and after the breaking of the 'long wave.' He makes a distinction between advanced and developing countries and between movements of goods, finance and labor. The World Economy examines the linkages of the global economy in some detail, including a discussion of OPEC, 'Reaganomics,' Latin American debt and the rise of Japan. Its comprehensive coverage includes Eastern Europe, China, India and Africa. This book will prove useful for students of international economics and international relations at all levels. Contents: Introduction; Incomes and the Welfare of Nations; Agrarian Economies; Advanced Economies; Interactions of the Core and the Periphery; OPEC 119; Japan and Southeast Asia; The United States; Western Europe; Australia and Canada; The USSR and Eastern Europe; China and India; Latin America; Africa
Keywords: "World economic conditions,1970 1987"